Project on Determining Vehicle Power in Submarine Vehicle Design Using Regression Analysis to Enhance Students Understanding of Simple Pendulum Concepts - Widya Rohmawati; Amos Isiaka Gambari; Anas Seidu Salifu (Tinta Emas Publisher, 2024)
This study aims to determine vehicle power in submarine vehicle design using regression analysis and enhance Students understanding of the simple pendulum concept. In this experiment, tests were conducted to analyze the relationship between various variables such as speed, force, and vehicle mass in relation to the power generated. The regression analysis results revealed a significant correlation between the applied force on the vehicle and the speed achieved, which was then used to calculate the required power for submarine vehicle design. Additionally, the study seeks to provide students with a deeper understanding of fundamental physics concepts, particularly the simple pendulum, by applying these concepts in the context of submarine vehicles. This research is expected to contribute to physics education and practical applications in vehicle design through regression-based analysis.